SENDING DRONE FLYING SPEED DATA USING ANDROID-BASED CLIENT SERVER METHOD - Putra, Daewu Gus Bintara; Kusumaningrum, Anggraini (Compiler, 2020)
Abstract - Drones as Unmanned Aerial Vehicle that are controlled using remote control are experiencing better development. The speed of the drone that cannot be accessed on the remote control can be determined through a client-server based application. The client side application, named Mydrone, is placed on the drone while on the server side, named Admin Drone, on earth. Mydrone and Admin Drone are applications made in this research based on andorid. This application on the client and server is used to monitor the speed of flying drones by using the Google Play Service library. Data sent from the client to the server in realtime by using Google Firebase. From the tests carried out it can be seen the speed of the drone when flying horisontal ly, while when flying vertically the speed is not detected. Battery capacity will also decrease when the speed of the drone gets faster, this is seen in the data when the speed is 8,741 km / h, the electricity demand taken from the battery is 31%.